Lotte Reiniger re-imagined - Kang, Fabian Yong Sheng (2019)
As homage to the works and innovations of German animator Lotte Reiniger, I present my FYP Lotte Reiniger Re-imagined (2019), an interactive installation space. Reiniger pioneered an avant-garde style of silhouette Trickfilm (animated film) using scissor paper-cuts and early stop-motion techniques. As an aesthetic response to her work and legacy, I am using Plato’s Cave as a point of departure to speak of the projection of shadows, by turning this idea in on itself, to escape the real world and embrace fantasy. The installation comprise two parts, Hier kommt die U-Bahn, a series of ball-point pen drawings of ‘real world’ 1920s Berlin in an exterior white-cube space; as well as Ein Abenteuer im Wunderwald, an interactive silhouette animation interface inside a black-box space. Wherein both spaces invite the viewer to move in and around them, traversing a realm of light and shadow, which reflects the magic of Reiniger’s work that inspired me to embark on this two year journey.